2020
DOI: 10.1037/dev0000826
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating ethnic-racial socialization among undocumented Latinx parents and its implications for adolescent psychosocial functioning.

Abstract: The purpose of this study is to examine how parents' documentation status informs their ethnic-racial socialization (ERS) practices and the subsequent implications for Latinx youths' psychological adjustment. The mixed-methods approach combined convergent and exploratory sequential designs to explore the breadth and depth of Latinx parents' messages to their children regarding race and ethnicity. Qualitative data were used to generate hypotheses that were tested quantitatively. Analysis of interviews revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 55 publications
1
64
0
Order By: Relevance
“…Among the most commonly explored were a sense of diminished social status, poor working and living conditions, discrimination, and the language barrier. These stressors are often the result of a systematic pattern of marginalization and disadvantage and have detrimental effects on the immigrant's mental health and that of his/her family system ( Brabeck et al., 2016 , Cross et al., 2020 ). Liminality or stress associated with having a limited sense of belonging also emerged as a significant stressor, which increased feelings of rejection and isolation, while also contributed to diminished self-identity ( Benuto et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the most commonly explored were a sense of diminished social status, poor working and living conditions, discrimination, and the language barrier. These stressors are often the result of a systematic pattern of marginalization and disadvantage and have detrimental effects on the immigrant's mental health and that of his/her family system ( Brabeck et al., 2016 , Cross et al., 2020 ). Liminality or stress associated with having a limited sense of belonging also emerged as a significant stressor, which increased feelings of rejection and isolation, while also contributed to diminished self-identity ( Benuto et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first limitation is that not enough studies with this hard‐to‐reach population have been conducted to fully understand the impact of undocumented status on children's and adults’ educational and mental health. The few studies that have examined these issues identify several risks associated with undocumented status for parents and children (Cross et al., 2020). Furthermore, it would be important to examine the possible protective effects of documentation status socialization, as this can potentially serve as a mechanism for healing from ethnic and racial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of the present study is to expand current understandings of ERS practices of Latinx parents to include documentation status socialization as an important ERS dimension for these families. Past ERS studies have indicated that Latinx undocumented parents differ in their ERS practices and approach to discussing immigration‐related issues with their youth (Ayón, 2016; Cross et al., 2020). Furthermore, previous research also indicates that the heightened anti‐immigrant sentiment and public rhetoric that resulted from the presidential campaign and election of US President Trump (2016–2020) has prompted difficult conversations regarding the threat of family separations amongst mixed status Latinx families (Ayón, 2016; Balderas et al., 2016; García, 2019).…”
Section: The Current Studymentioning
confidence: 99%
“…In a mixed-methods study with Latinx immigrant families (Cross et al, 2020) undocumented parents were found to employ the varied dimensions of ERS differently than documented ones. Quantitative analysis indicated that undocumented parents transmitted more cultural socialization messages than those of documented status.…”
Section: The Ethnic-racial Socialization Of Latinx Familiesmentioning
confidence: 94%
“…It also teaches children about their own nativity and documentation status, and rights that the youth are entitled to as U.S citizens. These parental teachings might also serve to counteract children's negative feelings associated with belonging to an immigrant family and foster family union (Ayón, 2016;Cross et al, 2020). Acknowledging documentation status socialization as an important ERS dimension (especially to Latinx immigrant families) will expand the ERS literature by improving our understanding of what and how parents have been communicating to their children regarding the impact of undocumented status on their family and community (Ayón, 2018;Cardoso et al, 2018;García, 2019).…”
mentioning
confidence: 99%